Mechanisms of Protection of the Lung - V. V. Moroz; L. M. Tuchina; G. G. Poroshenko (Общая реаниматология, 2005)
The lung has various mechanisms of protection from damaging action. There is mechanical protection of the lung from foreign exposures, which consists in the structural functional and morphological features governing the aerodynamic system, kinetic mechanisms (respiratory apparatus movement, bronchial motility, current surface alveolar layer movement), and blood and lymph flows. There are also nonspecific humoral and cellular factors of decontamination of foreign material (enzymatic reactions, natural cytotoxicity, pino- and phagocytosis of micro- and macrophages). Specific immune mechanisms are involved in the protection of the lung. Moreover, amongst the mechanisms of protectiong of the lung, the DNA reparation processes promoting the diminution of mutational processes occupy a certain place. Virtually all of these mechanisms are genetically controlled, i. e. are variously expressed in different persons.